Magnitude and determinants of stunting among children under five years of age in Ethiopia: a systematic review and meta-analysis - Elema, Teshome Bekele; Nega, Fetene; Ali, Jemal Mohammed; Edae, Gemechu; Boneya, Dube Jara (Frontiers in Pediatrics, 2025)
BackgroundThere is regional variation in the incidence of stunting, the most common of which occurs in Amhara, the largest share of which is in Ethiopia. However, evidence on the magnitude of stunting and its determinants in children under five years of age is inadequate. The objective of the current review is to identify, appraise, and review systematically and to analyze the pooled effect of stunting among children under the age of five in Ethiopia.Materials and methodsThe protocol of this review is registered in PROSPERO with registration number CRD42023323568 (https://www.crd.york.ac.uk). To combine the search results, we used reference management software (Endnote V-X7.2) and removed duplicates. For the meta-analysis, the Joanna Briggs Institute (JBI)-Meta-Analysis of Statistics Assessment and Review Instrument (MAStARI) was used for the critical appraisal of the studies. The data were categorized after extraction, sorted by quality score, and entered into STATA V14 for analysis. Cochrane's Q statistic (chi-square), I2, and p values were used to check for heterogeneity in the studies' outcomes.ResultsA total of 27 potentially eligible articles containing 32,448 under-five children were identified and included. The prevalence of stunting ranged from Eastern Hararghe (12.45%), the least prevalent to the highest prevalence, in the Tigray and Northwest regions (56.65%). Based on the meta-analysis, the overall pooled incidence of stunting was 40.30% (CI: 37.11–43.49 at 95% CI). The pooled effect size of twenty-seven studies showed that male children were 1.13 times more likely to have a risk of stunting than females (RR = 1.13, CI 1.01–1.26 @95%).Discussion and conclusionsChildhood stunting was significantly associated with the age of the child, child weight at birth, mother BMI, diarrhea episodes, deprivation of colostrum, and duration of breastfeeding. The issue of gender can be solved considering that breastfeeding duration was the lowest for daughters, as their parents were trying for a son. Finally, women's education is an alternative mechanism and sustainable strategy for overcoming the burden of childhood stunting.Systematic Review Registration[http://www.library.UCSF.edu], identifier [CRD42023323568].